Acoustical-perceptual correlates of 'whisper pitch' in synthetically generated vowels. - Higashikawa M; Minifie FD (Journal of Speech, Language & Hearing Research, 1999)
The purpose of this investigation was to clarify acoustical-perceptual relationships in identification of 'pitch' during whispered vowel production. The experimenters systematically varied selected acoustic features of synthetically generated 'whispered' vowels to control which formant frequencies were shifted (F1, F2, or F1&F2), the direction of formant frequency shifts (up or down), and the magnitude of formant frequency shifts (20 Hz, 40 Hz, 60 Hz). Two sets of stimuli were produced to simulate the resonance characteristics of the vowel /a/: one set for male talkers and one for female talkers. Ninety-four pairs of synthesized vowel tokens were randomly presented to 17 listeners who judged if the 'pitch' of the second member of the pair was the same, higher, or lower than the 'pitch' of the first member. The results showed an inverse relationship between the magnitude of formant frequency changes presented to the judges and the number of perceptual mismatches in 'whisper pitch.' Also, fewer mismatches in the identification of whisper pitch occurred when both F1 and F2 were changed simultaneously than when either F1 or F2 was changed individually. No differences were found between the perceptual responses to 'male' and 'female' vowel simulations. The primary implication of this study is that whisper pitch is more influenced by simultaneous changes in F1 and F2 than by changes in only one of the formants.